Glacier maxima in Baffin Bay during the Medieval Warm Period coeval with Norse settlement - Schweinsberg, Avriel D.; Schaefer, Joerg M.; Briner, Jason P.; Young, Nicolás E. (Science Advances, 2015)
The Baffin Bay region was relatively cool during the Medieval Warm Period coinciding with the period of Norse settlement.